PENGARUH PELATIHAN EMPATI MELALUI KARTU EKSPRESI EMOSI TERHADAP PERILAKU MENOLONG DAN PERILAKU AGRESIF PADA ANAK PRASEKOLAH - Zahro, Indah Fajrotuz (JCE (Journal of Childhood Education), 2017)
This study aims to determine the effect of empathy training through emotional expression cards on helpful behavior and aggressive behavior in preschool children. The subjects of this study are the group B children of Bina Anak Sholeh kindergarten Tuban. It uses purposive random sampling technique. A total of 28 children were sampled and divided into 14 children as experimental and control group. The instruments used are image tests of helpful behavior and aggressive behavior. Data were analyzed by using Mann Whitney U Test to test two independent samples using SPSS 16 for windows. From the data analysis, it isknown that hypotheses 1, 2, and 3 are accepted, namely 1) The positive effect of empathy training through emotional expression cards on helpful behavior and aggressive behavior in experimental and control group; 2) The positive effect of empathy training through emotional expression cards on helpul behavior ofpreschool children; 3) There is a negative effect of empathy training through emotional expression cards on aggressive behavior of preschool children.